109k views
2 votes
Awnserssss plsssssssssssssssssssssssss 18 points

Awnserssss plsssssssssssssssssssssssss 18 points-example-1
User GEMI
by
5.4k points

1 Answer

5 votes

Answer:

10. f'(x) = (x/14) + (14/9)

11. f'(x) = - x + 2

12. f'(x) = 2x - 8

Explanation:

The step to solving inverse is a simple trick. You must invert x and y.

For (10.) let f(x) = y

then y = 9x - 14

x = 9y - 14 (this is inverting x and y)

solving for y: x + 14 = 9y

therefore : y = (x/14) + (14/9)

You can do this for the others as well and using simple "solve for x" methods, you can solve for y which is f'(x).

User Kjell Rilbe
by
5.4k points